Case Report: Extensive Dermatitis Secondary to Severe Malnutrition, Zinc and Vitamin Deficiencies After Malabsorptive Bariatric Surgery - Herrera-Martínez, Aura D.; Junquera-Bañares, Sonia; Turrión-Merino, Lucía; Arrieta-Blanco, Francisco; Botella-Carretero, José; Vázquez-Martínez, Clotilde; Calañas-Continente, Alfonso (Frontiers in Endocrinology, 2021)
Bariatric surgery is an effective treatment for obesity and its comorbidities. However, it is not free of complications, especially when restrictive and malabsorptive techniques are combined. We present the case of a female patient whose obesity was treated with a biliopancreatic diversion. After twelve years of follow-up, she developed an extensive dermatitis secondary to zinc deficiency and malnutrition, precipitated by therapeutic non-compliance. A close surveillance of early symptoms and signs of nutritional deficiencies as well as chronic supplementation of vitamins and trace elements is required after bariatric surgery. This case illustrates the relevance of periodical, lifelong visits to a medical physician with special training and experience in the management of post bariatric surgery patients in order to prevent, diagnosis and early treat related complications.